Unusual Manifestations of Acute Cytomegalovirus Infection in Solid Organ Transplant Hosts: A Report of Two Cases - Alfredo Mena Lora; Justin Khine; Nadia Khosrodad; Vijay Yeldandi (Case Reports in Transplantation)
Cytomegalovirus (CMV) infection is a common cause of morbidity and mortality in immunocompromised hosts. Tissue-invasive CMV disease causing ulcerative skin disease or esophageal necrosis is rare. We herein describe two cases: a 47-year-old renal and pancreas transplant recipient who presented with skin ulcerations on his elbow and a 50-year-old renal transplant recipient who presented with acute esophageal necrosis. In both, tissue biopsy revealed CMV inclusion bodies by immunohistochemical staining of infected endothelial and mucosal cells. Ganciclovir was given to both cases and full remission occurred. Due to the varying presentations of acute CMV infection in immunosuppressed hosts, high suspicion and early tissue biopsy are vital for proper diagnosis and treatment when any suspicious cutaneous or mucosal manifestations are present.